PENGARUH MODEL PEMBELAJARAN LEARNING STARTS WITH A QUESTION (LSQ) TERHADAP KEMAMPUAN BERBICARA NARATIF SISWA KELAS IV SD MUHAMMADIYAH JONGAYA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Learning Starts with a Question (LSQ) learning model on the narrative speaking skills of fourth-grade students at Muhammadiyah Jongaya Elementary School. This study used a quantitative approach with a pre-experimental research design using a one-group pretest-posttest. The sample consisted of all 23 fourth-grade students. Data collection was conducted through narrative speaking skills tests administered before and after the treatment. The results showed an increase in students' narrative speaking skills after the LSQ model was implemented. The average pretest score of 56.25 increased to 82.25 in the posttest. This improvement indicates that the LSQ model is able to encourage students to be more active, confident in speaking, and able to construct stories coherently and systematically. Furthermore, the results of the hypothesis test indicate a significant effect of the LSQ learning model on students' narrative speaking skills.